PENGARUH GAYA HIDUP, PEMAHAMAN ETIKA KONSUMSI ISLAM DAN HALAL FESYEN TERHADAP PERILAKU KONSUMEN GENERASI Z PADA TREN FESYEN - Farah Sharfina (2023)
The process of globalization causes the development of technology and science in society and it is not uncommon for people to be helped by this technology. However, one of the impacts of this technological development is the occurrence of lifestyle changes in society through the internet which causes the emergence of consumptive behavior. The existence of the internet in society makes it easier for foreign cultures to enter Indonesia which causes lifestyle changes by changing the way of dressing that follows foreign cultures. It is not uncommon for people, especially in generation z who are still active in following the times, to buy fashion products continuously to fulfill their prestige and do not want to feel left behind by the development of trends in social media that are increasingly changing. The need for an understanding of Islamic consumption ethics to limit consumptive behavior in individuals. Therefore, researchers are interested in conducting research on this phenomenon using quantitative methods and are expected to provide new knowledge for readers. This study uses primary data with a purposive sampling method of 142 respondents using SPSS. The results of this study are that lifestyle, understanding of Islamic consumption ethics, and halal fashion have a significant effect on consumer behavior. From the results of previous research, it is hoped that this research will have new contributions for the Z generation and for those who read it. The limitation of this study is that it only uses three independent variables with the scope of research in Jabodetabek.